Aspek Keridhaan Dalam Komunikasi Bisnis Perspektif Tafsir Surah An-Nisaa’ Ayat 29 - Annisa Eka Rahayu; Kiki Zakiah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
This study aims to find out how to do business communication appropriately and effectively for the achievement of good aspects in a business or transaction. The pleasure aspect in a transaction is the most important element, because the pleasure aspect is one of the pillars of a transaction. There is no aspect of pleasure in a transaction, so it can be said that the transaction is facid (null). The research used is based on the normative juridical approach, namely by studying or analyzing secondary data in the form of library materials relating to the object of discussion The data analysis method used in this study is a qualitative method, with secondary data, namely in the form of books that are relating to business communication and interpretation of surah an-Nisaa 'verse 29. Aspect of pleasure in business is built through a true communication. The categories or elements of business communication so that the aspects of goodness can be achieved, including the honesty (fairness), elements of information accuracy and freedom of responsibility.